2016
DOI: 10.3389/fmars.2016.00146
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Pigments as Natural Anti-Hyperglycemic Agents: An In vitro Study

Abstract: Traditional medicines for controlling postprandial hyperglycemia includes herbs and plant extracts as well as synthetic drugs like acarbose. Synthetic drug molecules frequently have side effects such as flatulence and diarrhea. Cyanobacterial pigments have excellent anti-oxidant and free radical scavenging properties. Thus, α-amylase and α-glucosidase inhibiting activities of purified pigments and crude extracts from three cyanobacterial species, Lyngbya, Microcoleus, and Synechocystis sp., were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…With occurrence in animals, plants and microorganisms [ 24 , 25 , 26 , 27 ], the bioprospection of glucosidase inhibitors in sustainable natural sources was once concentrated on macroalgae [ 28 , 29 , 30 ] but it is interesting to look for alternatives with cheaper cultivation and that require less area, such as microalgae, including cyanobacteria [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The possibility of associating the production of these inhibitors with other metabolites of biotechnological interest produced by cyanobacteria, such as antioxidants [ 38 ]; pigments [ 39 ], acids and polysaccharides of cosmetic and pharmacological interest [ 40 , 41 ] in addition to joint production with polyhydroxybutyrate (PHB) [ 42 , 43 ] and biofuels [ 44 , 45 , 46 ], while mitigating CO 2 [ 43 , 44 ], is yet another advantage of this bacterial phylum.…”
Section: Introductionmentioning
confidence: 99%
“…With occurrence in animals, plants and microorganisms [ 24 , 25 , 26 , 27 ], the bioprospection of glucosidase inhibitors in sustainable natural sources was once concentrated on macroalgae [ 28 , 29 , 30 ] but it is interesting to look for alternatives with cheaper cultivation and that require less area, such as microalgae, including cyanobacteria [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The possibility of associating the production of these inhibitors with other metabolites of biotechnological interest produced by cyanobacteria, such as antioxidants [ 38 ]; pigments [ 39 ], acids and polysaccharides of cosmetic and pharmacological interest [ 40 , 41 ] in addition to joint production with polyhydroxybutyrate (PHB) [ 42 , 43 ] and biofuels [ 44 , 45 , 46 ], while mitigating CO 2 [ 43 , 44 ], is yet another advantage of this bacterial phylum.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated freezing at sub-zero temperatures followed by instant thawing is intended to shock and rupture the fragile cell walls and is considered to be one of the gentler techniques from the point of view of the proteins, since there is no heat generation involved. As such, it is one of the most common methods used for phycobiliprotein extraction (Soni et al, 2010;Mishra et al, 2011;Parmar et al, 2011;Ghosh et al, 2016Ghosh et al, , 2018Patel et al, 2018; with recoveries ranging from ∼29 to 102 mg g −1 of cell dry weight in the crude extract.…”
Section: Choice Of Buffer and Cell Disruption Methods Influence Cpe Extractionmentioning
confidence: 99%
“…C-phycoerythrin (CPE) is a water soluble, light harvesting accessory pigment found in some strains of cyanobacteria and is responsible for absorption of wavelengths inaccessible to chlorophyll. In addition to its role as a light harvesting protein, it is widely studied for its applications as a natural food colorant, anti-oxidant and anti-hyperglycemic agent, fluorescent tag, and small ion sensor (Sekar and Chandramohan, 2007;Ghosh et al, 2016Ghosh et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they proposed an antihyperglycaemic effect of Spirulina. Further, an in vitro study by Ghosh et al (2016) demonstrated the antihyperglycaemic effect of cyanobacterial pigments such as Figure 2. Anti-cancer activity associated with cyanobacteria (Luesch et al, 2001;Xiong et al, 2006;Yonezawa et al, 2012;Marquez et al, 2002;Drew et al, 2002).…”
Section: Cyanobacteria and Diabetesmentioning
confidence: 98%
“…In recent years several pharmaceutical companies have been working on "nutraceuticals", the term being a combination of the words "nutrition" and "pharmaceuticals" (Defelice, 1989) which can be defined as a food or food product that possesses health benefits and has medicinal properties in the prevention/treatment of disease (Dominguez, 2013;Kalra, 2003). Cyanobacteria are an important target due to their cosmopolitan availability and their bioactive compounds such as polyunsaturated fatty acids (PUFAs), phycobiliproteins (PBPs), carotenoids, several enzymes and vitamins, with a long history of use (Ciferri & Tiboni, 1985;Ghosh et al, 2016) due to their beneficial properties (Burja, Banaigs, Abou-Mansour, Burgess, & Wright, 2001;Nunnery, Mevers, & Gerwick, 2010;Singh, Kate, & Banerjee, 2005). Available evidence suggests that cyanobacteria have been used since 1500 BC to treat gout, fistula and forms of cancer (Abarzua, Jakubowski, Eckert, & Fuchs, 1999;Bhadury & Wright, 2004;Dahms, Ying, & Pfeiffer, 2006).…”
Section: Introductionmentioning
confidence: 99%